Integrating Peace Education in Literature Class - Istiani, Imas; Anam, Zuhrul (English Department, Faculty of Languages and Arts, Universitas Negeri Semarang, 2021)
The increasing cases of terrorism and extremism unite practitioners and theoreticians to put serious attention to the role of education for peacebuilding. However, finding an appropriate strategy connecting literature education to peacebuilding is challenging. Thus, the study explored the effectiveness of engaging suitable literary works to be used at schools to convey a peaceful message through To Kill a Mockingbird (TKAM) and The Kite Runner (TKR). The study was conducted in 4 classes of Literary Work Analysis course of IAIN Syekh Nurjati students in the second semester of 2018/2019 by applying Wahyudin’s (2018) five factors of peace education implementation in the classrooms. The study aimed to 1) investigate how to integrate peace education into the literature class and 2) elucidate the students' perception of peace education in the integrated literature class. It was found that applying peace education should consider 1) objectives, 2) subject contents, 3) methods and strategies, 4) media, and 5) learning evaluation. Students also perceived and learned about peace education by addressing some related issues in their papers and a survey.